Analysis of the Influence of Village Funds, the Family Hope Program and Direct Cash Assistance on the Human Development Index (HDI) in Pamekasan Regency - Andreanto Indra Pratama; M. Taufiq (Finance : International Journal of Management Finance, 2026)
The Human Development Index (HDI) is a benchmark for the success of quality of life development. This study analyzes the influence of the Village Fund (Dana Desa), Family Hope Program (PKH), and Cash Transfers (BLT) on HDI in Pamekasan Regency from 2014 to 2023. Using multiple linear regression, the results indicate that the Village Fund significantly contributes to HDI growth through infrastructure and basic health improvements. PKH and BLT provide social safety nets that stabilize community welfare, although their statistical significance varies. This research provides a comprehensive overview of how local and central government spending coordinates to improve human development indicators at the regency level.